2023
DOI: 10.1186/s40364-023-00491-8
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal glycosylation in glioma: related changes in biology, biomarkers and targeted therapy

Abstract: Glioma is a rapidly growing and aggressive primary malignant tumor of the central nervous system that can diffusely invade the brain tissue around, and the prognosis of patients is not significantly improved by traditional treatments. One of the most general posttranslational modifications of proteins is glycosylation, and the abnormal distribution of this modification in gliomas may shed light on how it affects biological behaviors of glioma cells, including proliferation, migration, and invasion, which may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 167 publications
1
5
0
Order By: Relevance
“…We describe the mevalonate, the N-glycan and the sphingolipid biosynthetic pathways, as induced pathways in HCC and thus potential targets for therapy. Although these new findings validate previous evidence of the role of these pathways in cancer cell survival and immune evasion (35, 3739, 45), such data is so far scarce and fragmented in HCC literature.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We describe the mevalonate, the N-glycan and the sphingolipid biosynthetic pathways, as induced pathways in HCC and thus potential targets for therapy. Although these new findings validate previous evidence of the role of these pathways in cancer cell survival and immune evasion (35, 3739, 45), such data is so far scarce and fragmented in HCC literature.…”
Section: Discussionsupporting
confidence: 77%
“…An abnormal glycosylation of the ectonucleotidase CD73 was found in HCC samples (36) but not in adjacent livers. More broadly, glycosylation patterns are known to be present in a variety of cancer type and contribute to its fitness and evasion from the immune surveillance (3739). Targeting ALG14 or RFT1 led to HCC cell death in a consistent fashion expanding a variety of cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Although great efforts have been made in recent years, there are still limitations in improving the prognosis of glioma. 6,7 With the development of nanoscience, nanomaterials and nanotechnology have been widely utilized in biology, medicine, and related fields, which have propelled the advancement of nanomedicine offering novel prospects for cancer therapy. One crucial facet of nanomedicine involves designing multifunctional drug delivery carriers using nanotechnology to develop new drug formulations and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma is the most prevalent malignant tumor of the nervous system. Despite significant progress in clinical treatment methods, such as surgery, chemotherapy, and radiation therapy, glioma remains prone to recurrence with almost irreversible side effects. , Although great efforts have been made in recent years, there are still limitations in improving the prognosis of glioma. , With the development of nanoscience, nanomaterials and nanotechnology have been widely utilized in biology, medicine, and related fields, which have propelled the advancement of nanomedicine offering novel prospects for cancer therapy. One crucial facet of nanomedicine involves designing multifunctional drug delivery carriers using nanotechnology to develop new drug formulations and therapeutics. Photodynamic (PDT) therapy is an indispensable technology that employs photosensitizers (PS) as PDT agents due to their localized impact on tumors with reduced adverse effects compared to conventional treatments while being minimally invasive with high spatial precision advantages making it a promising modality for treating gliomas. Photosensitizers can effectively generate cytotoxic reactive oxygen species (ROS) directly or indirectly, inducing tumor cell death through type I or type II PDT reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Unique alterations in tumor-associated glycosylation may also serve as a distinct feature of cancer cells and therefore provide novel diagnostic and even therapeutic targets [15]. It has been reported that abnormal glycosylation significantly impacts the proliferation and invasion of gliomas [16]. O-mannosylation, one type of O-linked mannose glycosylation, has also been implicated in cancer and metastasis [17].…”
Section: Introductionmentioning
confidence: 99%